IL-17A Promotes Intracellular Growth of Mycobacterium by Inhibiting Apoptosis of Infected Macrophages - Cruz, Andrea; Ludovico, Paula; Torrado, Egidio; Gama, José Bernardo; Sousa, Jeremy; Gaifem, Joana; Appelberg, Rui; Rodrigues, Fernando; Cooper, Andrea M.; Pedrosa, Jorge; Saraiva, Margarida; Castro, António G. (Frontiers in Immunology, 2015)
The fate of infected macrophages is a critical aspect of immunity to mycobacteria. By depriving the pathogen of its intracellular niche, apoptotic death of the infected macrophage has been shown to be an important mechanism to control bacterial growth. Here we show that IL-17 inhibits apoptosis of Mycobacterium bovis BCG- or M. tuberculosis-infected macrophages thus hampering their ability to control bacterial growth. Mechanistically, we show that IL-17 inhibits p53, and impacts on the intrinsic apoptotic pathway, by increasing the Bcl2 and decreasing Bax expression, decreasing cytochrome c release from the mitochondria, and inhibiting caspase-3 activation. The same effect of IL-17 was observed in infected macrophages upon blockade of p53 nuclear translocation. These results reveal a previously unappreciated role for the IL-17/p53 axis in the regulation of mycobacteria-induced apoptosis and can have important implications in a broad spectrum of diseases where apoptosis of the infected cell is an important host defense mechanism. .